Menjembatani kesenjangan digital: Peran bank syariah dalam memberdayakan UMKM melalui fintech syariah - Kamarullah, Khalifaturrahman (Maliki Interdisciplinary Journal, 2024)
Islamic fintech is crucial for driving the growth of MSMEs with principles of fairness and sustainability. This article discusses the potential of Islamic fintech in addressing digitalization challenges and expanding financial access for MSMEs. It identifies Islamic banks as key drivers in providing innovative technology-based financial solutions for small and medium enterprises (SMEs). However, negative stigma towards conventional fintech and the lack of understanding of Islamic values among the public hinder the implementation of Islamic fintech. One suggestion is that the public should be educated, technology should develop sustainably, there should be clear regulations, and there should be collaboration across industries. By implementing these recommendations, Islamic fintech can continue to grow and make a positive contribution to the growth of MSMEs and the Islamic economy.